PENGARUH MOTIVASI INTRINSIK TERHADAP PRESTASI KERJA KARYAWAN BATIK NAKULA SADEWA SLEMAN YOGYAKARTA - Armansyah, Armansyah; Fitriani, Dyah (Jurnal Fokus Manajemen Bisnis, 2012)
Current research aimed to investigate the effect of intrinsic motivation (the achievements, recognition of others, the work, opportunities to growth, responsibilities) both, partially and simultaneouslyÂ  employeeâ€™s performance. Respondent in this study were 35 employees of Nakula Sahadewa Sleman Yogyakarta Batik. This research used saturated techniques sampling. Analysis tool used in this research were multiple regression analysis, F test and t test. The results proved that intrinsic motivation simultaneously (F test) has a positive effect on emlpoyees performance. Whereas the t test showed that partially peconition of other, work, and responsibility employees has no significant effects on performance. Only achievement and oportunity to growth has significant effects on employees performance